Enhanced Photocatalytic Activity of Nanoparticle-Aggregated Ag–AgX(X = Cl, Br)@TiO2 Microspheres Under Visible Light - Zhang, Cuiling; Hua, Hao; Liu, Jianlin; Han, Xiangyu; Liu, Qipeng; Wei, Zidong; Shao, Chengbin; Hu, Chenguo (Nano-Micro Letters, 2017)
Ag–AgX(X = Cl, Br)@TiO2 nanoparticle-aggregated spheres with different mass ratio of R = TiO2/Ag(X) from 35:1 to 5:1 were synthesized by a facile sol–gel technique with post-photoreduction. The photocatalytic activities of both Ag–AgCl@TiO2 and Ag–AgBr@TiO2 under visible light are effectively improved by ~3 times relative to TiO2 NPAS under the simulated sunlight for the decomposition of methyl orange (MO). Ag–AgBr@TiO2 showed 30% improvement and less stable in photocatalytic activity than that of AgCl@TiO2. The role of Ag and AgX nanoparticles on the surface of Ag–AgX(X = Cl, Br)@TiO2 was discussed. Ag on these samples not only can efficiently harvest visible light especially for AgCl, but also efficiently separate excited electrons and holes via the fast electron transfer from AgX(X = Cl, Br) to metal Ag nanoparticles and then to TiO2-aggregated spheres on the surface of heterostructure. On the basis of their efficient and stable photocatalytic activities under visible-light irradiation, these photocatalysts could be widely used for degradation of organic pollutants in aqueous solution. Highlights: 1 Ag–AgX(X = Cl, Br)@TiO2 nanoparticle-aggregated spheres (NPAS) have been designed as a photocatalyst, in which AgX works as light harvester, Ag conducts as electron trapping and accumulating site, and TiO2 acts as electron collecting and photocatalytic site. 2 The photocatalytic activities of Ag–AgX(X = Cl, Br)@TiO2 by degradation of methyl orange (MO) under visible light were improved by ~3 times relative to TiO2 NPAS under simulated sunlight.